First coordination compounds based on a bis(imino nitroxide) biradical and 4f metal ions: synthesis, crystal structures and magnetic properties. Issue 7 (11th January 2016) - Reis, Samira G.; Briganti, Matteo; Martins, Daniel O. T. A.; Akpinar, Handan; Calancea, Sergiu; Guedes, Guilherme P.; Soriano, Stéphane; Andruh, Marius; Cassaro, Rafael A. A.; Lahti, Paul M.; Totti, Federico; Vaz, Maria G. F.
Abstract : The synthesis, structure and magnetic properties of lanthanide-biradical complexes are reported. Abstract : The synthesis, crystal structures and magnetic properties of two families of heterospin complexes containing lanthanide ions and a bis(imino nitroxide) biradical (IPhIN = 1-iodo-3, 5-bis(4′, 4′, 5′, 5′-tetramethyl-4′, 5′-dihydro-1 H -imidazole-1′-oxyl)benzene) are reported: in [Ln2 (hfac)6 (IPhIN)(H2 O)2 ] compounds, two lanthanide ions [Ln = Gd III (1 ) and Dy III (2 )] are coordinated to the biradical, and in [Ln(hfac)3 (IPhIN)(H2 O)] compounds, one lanthanide ion (Ln = Tb III (3 ), Gd III (4 ) or Dy III (5 )) is coordinated to the biradical. Ferromagnetic intramolecular magnetic interactions between Gd III and the biradical were found for1 and4, while intramolecular magnetic interactions between the radicals were ferro- and antiferromagnetic, respectively. Compound2 shows a field induced slow relaxation of magnetization, which (under an external applied field of 2 kOe) exhibits an activation energy barrier of Δ E / k B = 27 K and a pre-exponential factor of 1.4 × 10 −8 s. To support the magnetic characterization of compound3 ab initio calculations were also performed.